R(+)-Thioctic Acid Effects on Oxidative Stress and Peripheral Neuropathy in Type II Diabetic Patients: Preliminary Results by Electron Paramagnetic Resonance and Electroneurography. (10th April 2018) - Mrakic-Sposta, Simona; Vezzoli, Alessandra; Maderna, Luca; Gregorini, Francesca; Montorsi, Michela; Moretti, Sarah; Greco, Fulvia; Cova, Emanuela; Gussoni, Maristella
Abstract : Objectives . Diabetic neuropathy is the most common complication of diabetes. The idea of alterations in energy metabolism in diabetes is emerging. The biogenic antioxidant R(+)-thioctic acid has been successfully used in the treatment of diabetic polyneuropathic (DPN) patients. Methods . The effects of R(+)-thioctic acid (1 tablet, 1.6 g) administration were evaluated in 12 DPN patients at baseline and at 15, 30, 60, and 120 administration days throughout the assessment of oxidative stress (OxS); ROS production rate by electron paramagnetic resonance (EPR) technique; and oxidative damage biomarkers (thiobarbituric acid reactive substances (TBARS) and protein carbonyls (PC)), electroneurography (ENG) and visual analogue scale. Results . Supplementation induced significant changes (p < 0.05 ) at 30 and 60 days. ROS production rate up to −16%; TBARS (−31%), PC (−38%), and TAC up to +48%. Motor nerve conduction velocity in SPE and ulnar nerves (+22% and +16%) and sensor conduction velocity in sural and median nerves (+22% and +5%). Patients reported a general wellness sensation improvement (+35%) at 30 days: lower limb pain sensation (−40%) and upper limbs (−23%). Conclusion . The results strongly indicate that an increased antioxidant capacity plays an important role in OxS, nerve conduction velocity, pain, and general wellness improvement. Nevertheless, the effects of the antioxidant compound were found positive up to 60 days. Then, a hormesis effect was observed. Novelty of the research would be a challenge for investigators to carefully address issues, including dose range factors, appropriate administration time, and targeting population to counteract possible "boomerang effects." The great number of monitored parameters would firmly stress these conclusions.